What Drives the Payment of Higher Merger Premiums? - Soegiharto Soegiharto (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
This study examines whether the premiums paid to targets firms are affected by bidder CEO overconfidence, merger waves, method of payment, industry of merged firms, and capital liquidity. Using merger data for the period spanning from 1991 to 2000, this study finds that CEOs pay less premiums in cash mergers and pay more premiums for mergers undertaken during the year of high capital liquidity. Moreover, the findings also demonstrate that CEOs tend to pay higher merger premiums for mergers that occur during merger waves and in high capital liquidity year. CEOs’ behavior, which is the main variable examined in this study, does not show any significant effect on the premiums paid. This suggests that the effect of CEO overconfidence on the premiums paid may be exaggerated.